Overview of Taeniasis Disease Profile in North Toraja Regency, South Sulawesi Province - Yohana P; Afsahyana (Miracle Journal of Public Health, 2022)
Taeniasis is an infectious disease caused by tapeworms belonging to the genus Taenia in humans. This study aims to determine the description of the laboratory results of the incidence of Taeniasis in North Toraja Regency, South Sulawesi Province. The research method is descriptive. The samples obtained were 106 people. The survey results showed no Taenia worm eggs were found but the eggs of the worms Ascaris lumbricoides, Trichiuris trichiura, and Ancylostoma duodenale. The risk factors for personal hygiene are not cleaning themselves after taking care of livestock 0.9% and the risk factors for environmental sanitation are the type of clean water facilities in the form of springs 86.8%, not having latrines 1.9%, there is no place to dispose of livestock manure 95, 3%, and the distance of waterways ≤ 10 meters. It is necessary to provide counseling to people who have livestock and selective treatment to people with other worm infections.